Defining What is Good:: Pluralism and Healthcare Quality - Mitchell, Polly (Kennedy Inst Ethics J, 2019)
'Quality' is a widely invoked concept in healthcare, which broadly captures how good or bad a healthcare service is. While quality has long been thought to be multidimensional, and thus constitutively plural, we suggest that quality is also plural in a further sense, namely that different conceptions of quality are appropriately invoked in different contexts, for different purposes. Conceptual diversity in the definition and specification of quality in healthcare is, we argue, not only inevitable but also valuable. To treat one conception of healthcare quality as universally definitive of good healthcare unjustifiably constrains the ways in which healthcare can be understood to be better or worse. This indicates that there are limits to the extent to which improvement activities should be coordinated or standardized across the healthcare sector. While there are good reasons to advocate greater coordination in healthcare improvement activities, harmonization efforts should not advance conceptual uniformity about quality.